2008
DOI: 10.1038/sj.jid.5701074
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Is Activated in the Majority of Malignant Melanomas

Abstract: The objective of this study was to determine whether activation of the kinase mammalian target of rapamycin (mTOR) is associated with human melanoma. We found moderate or strong hyperphosphorylation of ribosomal protein S6 in 78/107 melanomas (73%). In contrast, only 3/67 benign nevi (4%) were moderately positive, and none were strongly positive. These data indicate that mTOR activation is very strongly associated with malignant, compared to benign, melanocytic lesions. Next, we tested six melanoma-derived cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 44 publications
6
132
1
Order By: Relevance
“…In favour to this interesting possibility is the observation that rapamycin and its analogues have efficacy in limiting the bone resorption mediated by osteoclastic cathepsin-k, 29 and can interfere with the proliferation of melanoma, a tumour exhibiting mTOR pathway activation, as well as MITF and cathepsin-k expression. 31,30,32 Finally, it is worth noting that abnormal bone mineral density has been demonstrated at high prevalence in lymphangioleiomyomatosis. 40 Although oestrogen deficiency has been hypothesized as a possible cause for the observed bone loss, 40 the possible influence of cathepsin-k overproduction, and/or the derangement of mTOR pathway in osteoclasts in lymphangioleiomyomatosis patients warrants further consideration in future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In favour to this interesting possibility is the observation that rapamycin and its analogues have efficacy in limiting the bone resorption mediated by osteoclastic cathepsin-k, 29 and can interfere with the proliferation of melanoma, a tumour exhibiting mTOR pathway activation, as well as MITF and cathepsin-k expression. 31,30,32 Finally, it is worth noting that abnormal bone mineral density has been demonstrated at high prevalence in lymphangioleiomyomatosis. 40 Although oestrogen deficiency has been hypothesized as a possible cause for the observed bone loss, 40 the possible influence of cathepsin-k overproduction, and/or the derangement of mTOR pathway in osteoclasts in lymphangioleiomyomatosis patients warrants further consideration in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Interestingly, the expression of cathepsin-k in osteoclasts is regulated by MITF 28 and is significantly reduced by mTOR inhibitors. 29 MITF and cathepsin-k are also expressed in melanocytes and melanomas, 30 where mTOR is also activated and critical for the regulation of apoptosis. 31,32 All these data taken together, it is possible to hypothesize that MITF and cathepsink are in fact under the control of mTOR pathway, and could serve as further molecular markers for evaluating mTOR pathway activation in lymphangioleiomyomatosis.…”
Section: Recently Kenerson Et Almentioning
confidence: 99%
“…21 Mammalian target of rapamycin (mTOR) activation is also strongly associated with MM compared to benign melanocytic lesions. 22 Endostatin levels were elevated in stage III and stage IV melanoma patients compared to healthy control individuals, and endostatin levels might have a utility for disease monitoring. 23 Animal studies revealed the efficacy of recombinant endostatin to suppress melanoma tumor growth and melanoma metastasis formation.…”
Section: Fibrohistiocytic Tumorsmentioning
confidence: 95%
“…There is evidence from the literature that mTOR signalling is active in melanoma. Studies have shown the presence of constitutive phospho-S6K in a high proportion of metastatic melanoma samples (Karbowniczek et al, 2008). Further work has shown that rapamycin has growth inhibitory effects across a panel of human melanoma cell lines (Molhoek et al, 2005), and there is evidence of synergistic pro-apoptotic activity between sorafenib/MEK inhibitors and rapamycin in preclinical models of melanoma (Molhoek et al, 2005;Meier et al, 2007;Lasithiotakis et al, 2008).…”
Section: Suitable Combination Targets: Mtor Signalling?mentioning
confidence: 99%